TOKYO’S EURASIAN DIPLOMACY: SUCCESSES AND FAILURES (1997-2017) - O. G. Paramonov; O. V. Puzanova (Сравнительная политика)
This article is devoted to the analysis of the growing importance of the Eurasian direction in Japan's foreign policy, the causes and consequences of the duality and inconsistency of this policy, the influence of internal political reasons on Japan's alignment with its policy towards the Central Asian states. The process of building up a new system of Japan’s foreign policy behavior in Central Asiain this case has developed in a reactive as opposed to a proactive manner. Eurasian direction of Japan’s diplomacy demanded a serious revision because by the new project «One Belt, One Road», which is an unprecedented regional initiative of Beijing– the primary foreign policy opponent for Tokyo. The regional agenda of Tokyois also influenced by the new approaches of Donald Trump’s administration to the multilateral cooperation’s forms. Tokyo’s attempts to pursue its relations with the Central Asian states as a whole region and the Japan’s experience of using the dialogue «Central Asia plus Japan» as a promising model for the cooperation between non-regional actors and its Central Asia’s partners, are also of interest. In addition, the article deals with the preconditions for coordinating actions in the Eurasian direction between Japan and its friendly states, including Turkey and India, and the process of diversifying the economic partners of the Central Asian region as a whole. Since the reasons for the interest of the Central Asian states in the implementation of economic and other forms of cooperation with Tokyohave not lost their relevance, Russiacould be of significant value to Tokyo.